Leveraging Technology and Human Capital Development for Productivity Enhancement: A Case Study of The Transformer Project - I Gusti Bagus Aditya; rer. nat. Filiana Santoso; Maulahikmah Galinium (ILTEK : Jurnal Teknologi, 2026)
Despite Indonesia’s coal output surpassing 775 million tons in 2023, contractors continue to face inefficiencies due to low equipment utilization, inconsistent operator discipline, and weak digital integration. This study examines The Transformer Project, a collaboration between PT XYZ and PT United Tractors, combining Prodigy (real-time monitoring system) and Coretana (competency-based training) to enhance Komatsu PC1250 excavator performance. A sequential explanatory mixed-method approach was employed: FGDs and root cause analysis, a TAM survey validated through SEM, and KPI-based performance measurement. Results indicate weak explanatory power of TAM (R² = 5.6%), yet the interventions achieved substantial operational improvements: productivity increased by 47%, idle time decreased by 15%, fuel efficiency improved by 10%, and operator competency rose by 19%. The findings suggest that in capital-intensive industries, technology adoption is shaped more by organizational enforcement and KPI-driven incentives rather than individual perception, highlighting the need for extended adoption models.